Pendampingan Masyarakat Dalam Upaya Pengembangan Sentra Produksi Jagung Hibrida di Desa Morome Kabupaten Konawe Selatan Sulawesi Tenggara - Lely Okmawaty Anwar; Sri Fatma Sari; Mustam Mustam; Latifa Fekri (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The aim of assistance is to improve the economy of the Morome Village community by increasing the production of hybrid maize. Implementation is carried out using the Integrated Crop Management (PTT) system method, which is an innovative and dynamic approach in an effort to increase production and farmer income through participatory assembly of technology components with farmers. The results of the assistance showed an increase in the production of dry-shelled hybrid maize 4,250 kg/hectare with an RC ratio of 2, with a profit of IDR 6,905,000/hectare. Integrated crop management is highly recommended to continue to be applied in all maize areas as an effort to develop hybrid maize production.